A Research on Market Orientation of SMES in India: A Qualitiative Approach. - Jaggi, Rajiv Raja (2007)
Market orientation is a very challenging subject in the marketing literature and its significance is being recognised gradually in theoretically as well in practical application. There have been various studies showing the positive effect of market orientation on the performance of large firms. But there has not been enough research about the market orientation of small and medium enterprises (SMEs). Taking into consideration the growing importance of SME sector in various economies especially in case of developing countries like India, understanding the market orientation in SMEs and the problems faced by these firms can give a competitive edge to such firms. The purpose of this analysis is to portray the relationship between these small and medium-sized enterprises (SMEs) and marketing, i.e., what are the actual practices with respect to marketing especially in context of Indian industry. Data is gathered by adopting a sampling strategy making use of questionnaires and telephonic interviews, the answers to which are given by 30 SMEs managers and owners across India. By analysing the feedbacks received, this paper has been able to explore and scrutinize in detail the knowledge and awareness of managers and owners regarding the concept of market orientation and whether SMEs in India apply market orientation in their business. The primary goal of the research was to access and understand the different conceptions that managers and owners hold about market orientation. The results of the research portray overall view about the research question rather than a single or specific result.